2021
DOI: 10.3390/antiox10101559
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ROS Generation by Extract of Warburgia ugandensis Leading to G0/G1 Cell Cycle Arrest and Antiproliferation in A549 Cells

Abstract: Warburgia ugandensis Sprague (WU) is a traditional medicinal plant used for the treatment of various diseases, including cancer, in Africa. This study aimed to evaluate the anti-non-small cell lung cancer (NSCLC) activities of WU against A549 cells and to reveal potential molecular mechanisms. The cytotoxicity of various WU extracts was evaluated with HeLa (cervical cancer), HepG2 (liver cancer), HT-29 (colorectal cancer), and A549 (non-small cell lung cancer) cells by means of Sulforhodamine B (SRB) assay. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Interestingly, the antiproliferative effects of 64 and 73 can be terminated by the addition of the antioxidant N-acetyl cysteine (NAC), suggesting that ROS play a critical role in the mode of action of drimanes by inducing DNA damage. Increased ROS and γH2AX levels were also observed in HT-29 and HCT116 and A549 cells after incubation with extracts of W. ugandensis [130,131]. In addition to that, extracts of W. ugandensis lead to an increase in c-PARP1 concentrations.…”
Section: Ros Generation and Dna Damagementioning
confidence: 80%
See 2 more Smart Citations
“…Interestingly, the antiproliferative effects of 64 and 73 can be terminated by the addition of the antioxidant N-acetyl cysteine (NAC), suggesting that ROS play a critical role in the mode of action of drimanes by inducing DNA damage. Increased ROS and γH2AX levels were also observed in HT-29 and HCT116 and A549 cells after incubation with extracts of W. ugandensis [130,131]. In addition to that, extracts of W. ugandensis lead to an increase in c-PARP1 concentrations.…”
Section: Ros Generation and Dna Damagementioning
confidence: 80%
“…Zhang et al observed reduced expression of cyclin D1 and E1 after exposure of A549, HT-29, and HCT 116 cells to the extract of the W. ugandensis [130,131]. Cyclin D1 and E1 play an important role in the progression from the G 1 to the S phase [138,139].…”
Section: Cell Cycle Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the above hypothesis, we treated HCC cells with N‐acetyl‐L‐cysteine (NAC), a ROS inhibitor, 24 together with Cu(sal)(phen). As represented in Figure 2B, the ROS content induced by Cu(sal)(phen) in both HCC cell lines was significantly reduced by NAC cotreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that ROS and their derivatives are closely associated with cell apoptosis. 23 To further investigate the To verify the above hypothesis, we treated HCC cells with N-acetyl-L-cysteine (NAC), a ROS inhibitor, 24 together with Cu(sal)(phen).…”
Section: Effects Of Cu(sal)(phen) On Ros Levels In Hcc Cellsmentioning
confidence: 99%